2018
DOI: 10.3390/foods7070106
|View full text |Cite
|
Sign up to set email alerts
|

Novel Food Processing and Extraction Technologies of High-Added Value Compounds from Plant Materials

Abstract: Some functional foods contain biologically active compounds (BAC) that can be derived from various biological sources (fruits, vegetables, medicinal plants, wastes, and by-products). Global food markets demand foods from plant materials that are “safe”, “fresh”, “natural”, and with “nutritional value” while processed in sustainable ways. Functional foods commonly incorporate some plant extract(s) rich with BACs produced by conventional extraction. This approach implies negative thermal influences on extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 184 publications
(110 citation statements)
references
References 136 publications
0
92
0
2
Order By: Relevance
“…Different previous research studies confirmed the positive impact of sonication treatment on the content of polyphenolic compounds: total phenols, flavonoids, phenolic acids, flavones, flavonols, etc. [21,23,[28][29][30][31]. Namely, besides cell wall destruction as a direct mechanical result of transient cavitation, different reactions at the chemical level can occur during sonication [32,33].…”
Section: Bioactive Content and Antioxidant Capacity Of The Different mentioning
confidence: 99%
“…Different previous research studies confirmed the positive impact of sonication treatment on the content of polyphenolic compounds: total phenols, flavonoids, phenolic acids, flavones, flavonols, etc. [21,23,[28][29][30][31]. Namely, besides cell wall destruction as a direct mechanical result of transient cavitation, different reactions at the chemical level can occur during sonication [32,33].…”
Section: Bioactive Content and Antioxidant Capacity Of The Different mentioning
confidence: 99%
“…They are commonly consumed in its raw form or as processed products, such as jellies, preserves, syrups, and juices. Modern consumers tend to show interests for the foods that are fresh, authentic, and with high physicochemical and nutritional qualities, while same applies for the fruit juices (Granato et al, ; Putnik et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…animal wastes, flowers, herbs, agrifood by-products) ( Table 3). 127 Moreover, the main advantages associated with this technology are the improved extraction yield, reduced time to obtain the compounds and also the use of green solvents. For instance, the extraction of ferulic acid (an antioxidant, antimicrobial and inducer of brain blow flow) from radix (Angelica sinensis) was improved by the use of HP.…”
Section: Application Of Hp In Sustainable Extractionmentioning
confidence: 99%